2019
DOI: 10.1021/acs.jafc.8b07021
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantitation of 12 Volatile Aldehyde Compounds in Wine by LC-QQQ-MS: A Combined Measure of Free and Hydrogen-Sulfite-Bound Forms

Abstract: This work outlines a rapid novel methodology for the direct quantitation of 12 volatile aldehyde compounds related to oxidative off-flavors in wine, by measuring the combined free and hydrogen-sulfite-bound forms of each aldehyde compound, consisting of four general aldehydes, four Strecker aldehydes, and four (E)-2-alkenals. The methodology requires minimal preparation of wine samples: the addition of internal standards and 6 g/L sulfur dioxide, and filtration prior to quantitation by liquid chromatography-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…UF treatment and heating of retentate did not significantly change 3-methylbutanal, ( E )-2-nonenal and 2-phenylacetaldehyde concentrations in wine. Results of 3-methylbutanal were much lower than previously measured in commercial wines ( 58 ). These results showed that UF/heat/protease treatments did not introduce oxidative characters to wine.…”
Section: Resultscontrasting
confidence: 79%
“…UF treatment and heating of retentate did not significantly change 3-methylbutanal, ( E )-2-nonenal and 2-phenylacetaldehyde concentrations in wine. Results of 3-methylbutanal were much lower than previously measured in commercial wines ( 58 ). These results showed that UF/heat/protease treatments did not introduce oxidative characters to wine.…”
Section: Resultscontrasting
confidence: 79%
“…Free and total concentrations of SO 2 were directly quantified by a FIAStar 5000 analyzer (FOSS, Melbourne, Victoria, Australia). Total metal concentrations were measured by inductively coupled plasma optical emission spectrometry (ICP–OES, Varian 710, Varian, Palo Alto, CA, U.S.A.) as described by Rousseva et al Non-sulfide-bound Cu was determined by medium-exchange constant current stripping potentiometry (ME-CCSP) with screen-printed carbon electrodes as described by Clark et al The total concentrations of volatile aldehyde compounds were determined by liquid chromatography triple quadrupole mass spectrometry (LC–QQQ–MS, Agilent 6400 LC system and Agilent 6470 Triple Quardrupole MS system, Agilent Technologies Australia) as described by Zhang et al Esters, C 6 compounds, terpenes, and lactones were quantified by headspace solid-phase microextraction (HS-SPME) coupled to gas chromatography–mass spectrometry (GC–MS, Agilent 7890 GC and Agilent 5975C MS system, Agilent Technologies Australia) as per Šuklje et al Wine color parameters were measured by a spectrophotometer (UV-1700, Shimadzu, Kyoto, Japan) according to Iland et al…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Free and total concentrations of SO 2 were directly quantified by a FIAStar 5000 analyzer (FOSS, Melbourne, Victoria, Australia). Total metal concentrations were measured by inductively coupled plasma optical emission spectrometry (ICP−OES, Varian 710, Varian, Palo Alto, CA, U.S.A.) as described by Rousseva et al 44 Non-sulfide-bound Cu was determined by medium-exchange constant current stripping potentiometry (ME-CCSP) with screen-printed carbon electrodes as described by Clark et al 45 The total concentrations of volatile aldehyde compounds were determined by liquid chromatography triple quadrupole mass spectrometry (LC−QQQ−MS, Agilent 6400 LC system and Agilent 6470 Triple Quardrupole MS system, Agilent Technologies Australia) as described by Zhang et al 46 Esters, C 6 compounds, terpenes, and lactones were quantified by headspace solid-phase microextraction (HS-SPME) coupled to gas chromatography−mass spectrometry (GC−MS, Agilent 7890 GC and Agilent 5975C MS system, Agilent Technologies Australia) as per S ̌uklje et al 47 Wine color parameters were measured by a spectrophotometer (UV-1700, Shimadzu, Kyoto, Japan) according to Iland et al 48 LMWSCs (total) were analyzed by headspace injection gas chromatography (GC, Agilent 7890B GC system, Agilent Technologies Australia, Mulgrave, Victoria, Australia) connected to a sulfur chemiluminescence detector (SCD, Agilent 355 SCD, Agilent Technologies Australia), as described by Rousseva et al 44 Prior to LMWSC analysis, samples were treated as per Siebert et al, 49 whereby 10 mL of wine sample was transferred into a 20 mL headspace vial containing 3 g of sodium chloride, and 100 μg/L of ethyl methyl sulfide was added as an internal standard.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas-chromatography (GC, Agilent 7890B GC system, Agilent Technologies Australia, Mulgrave, VIC, Australia) and sulfur chemiluminescence detector (SCD, Agilent 355 SCD, Agilent Technologies Australia) conditions were set up as per Rousseva et al [35], and a DB-Sulfur SCD column (60 m, 0.32 mm, 4.2 µm, Agilent J&W Scientific, Agilent Technologies Australia) was utilized. The concentrations of volatile aldehyde compounds in wine were quantified by liquid-chromatography-QQQ-mass spectrometry (LC-QQQ-MS, Agilent 6400 LC system, and Agilent 6470 Triple Quardrupole MS system, Agilent Technologies Australia) as per Zhang et al [38]. The column used for this technique was an Acquity UPLC BEH C18 column (1.7 µm, 2.1 mm × 50 mm, Waters Australia, Rydalmere, NSW, Australia).…”
Section: Juice Must and Wine Compositional Analysesmentioning
confidence: 99%